Regulation of Eosinophil Recruitment and Activation by Galectins in Allergic Asthma - Rao, Savita P.; Ge, Xiao Na; Sriramarao, P. (Frontiers in Medicine, 2017)
Eosinophils are differentiated granulocytes that are recruited from the bone marrow to sites of inflammation via the vascular system. Allergic asthma is characterized by the presence of large numbers of eosinophils in the lungs and airways. Due to their capacity to rapidly release inflammatory mediators such as cytokines, chemokines, growth factors and cytotoxic granule proteins upon stimulation, eosinophils play a critical role in pro-inflammatory processes in allergen-exposed lungs. Identifying key players and understanding the molecular mechanisms directing eosinophil trafficking and recruitment to inflamed airways is a key to developing therapeutic strategies to limit their influx. Recent studies have brought to light the important role of glycans and glycan binding proteins in regulating recruitment of eosinophils. In addition to the role of previously identified eosinophil- and endothelial-expressed adhesion molecules in mediating eosinophil trafficking and recruitment to the inflamed airways, studies have also indicated a role for galectins (galectin-3) in this process. Galectins are mammalian lectins expressed by various cell types including eosinophils. Intracellularly, they can regulate biological processes such as cell motility. Extracellularly, galectins interact with β-galactosides in cell surface-expressed glycans to regulate cellular responses like production of inflammatory mediators, cell adhesion, migration and apoptosis. Eosinophils express galectins intracellularly or on the cell surface where they interact with cell surface glycoconjugate receptors. Depending on the type (galectin-1, -3, etc.) and location (extracellular or intracellular, endogenous or exogenously delivered), galectins differentially regulate eosinophil recruitment, activation and apoptosis and thus exert a pro- or anti-inflammatory outcome. Here we have reviewed information pertaining to galectins (galectin-1, -3 -9 and -10) that are expressed by eosinophils themselves and/or other cells that play a role in eosinophil recruitment and function in the context of allergic asthma and their potential use as disease bio-markers or therapeutic targets for immunomodulation.